Advancing sustainable aquaculture: Integrating offshore and coastal practices for maritime sustainability - S. Suhartini; Larsen Barasa (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
Sustainable aquaculture is essential to meeting the growing global demand for seafood while addressing environmental and socio-economic challenges. This research explores the integration of offshore and coastal aquaculture systems, emphasizing their complementary roles in achieving sustainability within the maritime domain. Offshore systems, characterized by advanced technological innovations, demonstrated superior nutrient cycling efficiency and structural resilience. In contrast, coastal systems excelled in habitat preservation and cost efficiency through ecosystem-based practices. Using a qualitative methodology, the study involved semi-structured interviews with 13 maritime professionals, 24 educators, and 33 graduates, supported by thematic analysis and observational data. The findings revealed the critical role of interdisciplinary collaboration, with educators leading knowledge-sharing efforts, professionals offering practical insights, and graduates contributing innovative ideas. The research concludes that integrating these systems can maximize aquaculture productivity, reduce environmental impacts, and support socio-economic development. Additionally, embedding sustainability principles into maritime education ensures that future professionals are equipped to implement innovative solutions. This study provides actionable recommendations for advancing aquaculture technologies, fostering stakeholder collaboration, and promoting sustainability in the maritime industry.